The Management of Natural Resources in Tourist Destinations: Challenges and Their Future Potential in Bali - Pambud, Bondan; Darsanai, Made (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
Bali offers a compelling case study for understanding the complex challenges of managing natural resources in a tourism-intensive setting. The island’s natural beauty, cultural richness, and biodiversity have made it a global tourism hotspot, yet these assets are increasingly threatened by over-tourism, water scarcity, unmanaged waste, and land-use conversion. This study adopts a qualitative approach using a library-based case study method, drawing on academic literature, government reports, legal frameworks, environmental data, and policy documents to analyze the ecological, socio-cultural, and governance dynamics of resource management in Bali. The findings highlight critical issues such as excessive groundwater extraction by the hospitality sector, inadequate waste management systems leading to marine and land pollution, and deforestation driven by tourism infrastructure development. Despite these challenges, Bali demonstrates significant potential through its cultural philosophy of Tri Hita Karana, policy instruments like Law No. 15 of 2023 and RTRW 2020, and growing innovations in community-based tourism, renewable energy, and participatory governance. The study concludes that Bali’s future sustainability depends on the integration of traditional values with regulatory enforcement, inclusive stakeholder collaboration, and adaptive environmental management. If implemented holistically, these strategies can position Bali as a global model for sustainable tourism rooted in cultural integrity and ecological resilience.